Typification of the Iberian endemic Juniper Juniperus navicularis Gand. (Cupressaceae) - Ferreira, Catarina; Jiménez, Carlos; Serrano, Miguel; Vieira, Cristiana; Vila-Viçosa, Carlos (Phytotaxa, 2024)
The typification of the name Juniperus navicularis (Cupressaceae) is provided, based on a thorough literature review and examination of original herbarium material deposited in the Gandoger collection (LY). In addition to discussing the historical background of the name and various assignments by different authors, we further studied additional types from Portuguese collections (LISU, COI, and PO) and other historical herbaria (H and P), cited in the species protologue.